Blade design and analysis for steam turbines - Singh, Murari P.; Lucas, George M. (New York : McGraw-Hill, 2011)
'THE LATEST STEAM TURBINE BLADE DESIGN AND ANALYTICAL TECHNIQUESBlade Design and Analysis for Steam Turbines provides a concise reference for practicing engineers involved in the design, specification, and evaluation of industrial steam turbines, particularly critical process compressor drivers. A unified view of blade design concepts and techniques is presented. The book covers advances in modal analysis, fatigue and creep analysis, and aerodynamic theories, along with an overview of commonly used materials and manufacturing processes. This authoritative guide will aid in the design of powerful, efficient, and reliable turbines.COVERAGE INCLUDES: Performance fundamentals and blade loading determination Turbine blade construction, materials, and manufacture System of stress and damage mechanisms Fundamentals of vibration Damping concepts applicable to turbine blades Bladed disk systems Reliability evaluation for blade design Blade life assessment aspects Estimation of risk'--Provided by publisher.
'Blade Design and Analysis for Steam Turbines details blade functionality and how it fits in relation to the complete steam turbine system as well as construction materials and methods, manufacturing processes, and design methods to estimate reliability of blades under fatigue and vibration. Blades are at the heart of process steam turbines used to generate electricity from wind, steam, gas, and solar hydrogen. The information in this book helps turbine designers, mechanical engineers, process equipment design/maintenance engineers, and buyers of turbines estimate the reliability of blades'--Provided by publisher.
Includes bibliographical references (p. 347-350) and index.
Keywords: Steam-turbines -- Blades -- Design and construction